Commercial gaming devices for stroke upper limb rehabilitation: a survey of current practice. (17th August 2016) - Thomson, Katie; Pollock, Alex; Bugge, Carol; Brady, Marian C.
Abstract: Purpose : Stroke upper limb impairment is associated with disability in activities of daily living. Gaming (Nintendo Wii) is being introduced to rehabilitation despite limited evidence regarding effectiveness. Little data exists on how gaming is implemented resulting in a lack of clinical information. We aimed to gather therapists' opinions on gaming. Methods : A survey was posted to therapists, identified from stroke services across Scotland. A second survey was posted to non-responders. Survey data were analysed using descriptive statistics and thematic coding. Results : Surveys were sent to 127 therapists (70 stroke services) and returned by 88% (112/127). Gaming was used by 18% of therapists, 61% (68/112) stated they would use this intervention should equipment be available. The most commonly used device was Nintendo Wii (83% of therapists using gaming) for 30 min or less once or twice per week. Half of therapists (51%) reported observing at least one adverse event, such as fatigue, stiffness or pain. Gaming was reported to be enjoyable but therapists described barriers, which relate to time, space and cost. Conclusions : Gaming is used by almost a fifth of therapists. Adverse events were reported by 51% of therapists; this should be considered when recommending use and dosage. Implications for Rehabilitation: Commercial gaming devices are reported to be used by 1/5th of therapists for stroke upper limb rehabilitation, 3/5ths would use gaming if available. Adverse events were reported by 51% of therapists; this should be considered when recommending use and dosage. Current use of gaming in practice may not be achieving intense and repetitive upper limb task-specific practice.